Site-Directed Mutations at Phosphorylation Sites in Zea mays PHO1 Reveal Modulation of Enzymatic Activity by Phosphorylation at S566 in the L80 Region - Noman Shoaib; Nishbah Mughal; Lun Liu; Ali Raza; Leiyang Shen; Guowu Yu (Plants, 2023)
Starch phosphorylase (PHO) is a pivotal enzyme within the GT35-glycogen–phosphorylase (GT; glycosyltransferases) superfamily. Despite the ongoing debate surrounding the precise role of PHO1, evidence points to its substantial influence on starch biosynthesis, supported by its gene expression profile and subcellular localization. Key to PHO1 function is the enzymatic regulation via phosphorylation; a myriad of such modification sites has been unveiled in model crops. However, the functional implications of these sites remain to be elucidated. In this study, we utilized site-directed mutagenesis on the phosphorylation sites of Zea mays PHO1, replacing serine residues with alanine, glutamic acid, and aspartic acid, to discern the effects of phosphorylation. Our findings indicate that phosphorylation exerts no impact on the stability or localization of PHO1. Nonetheless, our enzymatic assays unveiled a crucial role for phosphorylation at the S566 residue within the L80 region of the PHO1 structure, suggesting a potential modulation or enhancement of PHO1 activity. These data advance our understanding of starch biosynthesis regulation and present potential targets for crop yield optimization.